Winters of avalanche maximum in the Greater Caucasus for the period of instrumental observations (1968–2016) - A. D. Oleinikov; N. A. Volodicheva (Лëд и снег)
This investigation has been carried out to identify winters with the maximum frequency of avalanches in the Greater Caucasus. The analysis was performed for decades and for the entire period of instrumental observations (1968–2016). We chose severe snow winters which were followed by releases of particularly large and heavy avalanches (Lmax) and the maximum area of damage to the mountain territory during the study period. The following materials were used for this work: 1) 47‑year-old (1968–2016) series of data on snow avalanches from observations performed at the high-altitude station of the Faculty of Geography of the Lomonosov Moscow State University in the near-Elbrus area (Central Caucasus); 2) the results of winter and summer investigations of snow and avalanches in Arkhyz (the Western Caucasus); 3) materials of field works carried out in the Caucasus at different times; 4) the results of winter typing from data of 41 mid- and high-mountain meteorological stations in the Greater Caucasus; 5) literature sources; 6) survey data. The dependence of avalanche activity on the types of winters was established for key observational sites in the near-Elbrus area (Central Caucasus) and Arkhyz (Western Caucasus). This dependence formed the basis for determining the Lmax winters from factors of the avalanche formation, i.e. the air temperature and precipitation for the cold period from meteorological observations. Based on the method of winter typing, the winters of the maximal avalanche occurrence were estimated from data of 41 meteorological stations of the Greater Caucasus for 1936–2016. Results of the typing revealed similar avalanche extremes as it was found from direct observations of releases of snow avalanches: on the Southern macro-slope of the Western and Central Caucasus – 1986/87; on the Eastern Caucasus – 1971/72. Two seasons, claiming the role of the Lmax – 1967/68 and 1975/76, were revealed on the Northern macro-slope.